PENGARUH ROKOK TERHADAP JUMLAH SEL SPERMATOZOA MENCIT JANTAN (Mus Musculus, Strain Jepang) - Putra, Yuhendri (IAIN Batusangkar, 2014)
The purpose of this research is to know more about the influence of cigarette?s smoke to the quantity, mouse?s spermatozoa during one cycle of spermatogenesis. This research used the method of Post Test Only Control Group Design. The sample is about 24 male mice which criteria 2-3 month old, male, 25-35 gr weight. The result of the research to quantity of spermatozoa by Anova test showed the significant connection (?> 0.05) between control group with behavior, average the spermatozoa motility decrease if compare with control. Preferable if we want to know more about the influence of cigarette to the quality of sperm, we will need a test to the other quality suvh pH, velocity, viscosity and DNA of spermatoza.Key words : quality of spermatozoa, cigarettes, male mouse